Perceptions of Psychopedagogy Students in Argentina Regarding their Empathic Capacity in Developing their Professional Identity - Schlegel, Daiana (2021)
Empathy is one of the most important socio-emotional competencies for anyone who works in the field of Education. This study aims to identify perceptions of an advanced group of Psychopedagogy Majors regarding their ability to empathize. The study design was cross-sectional, descriptive and quantitative. During the 2019 school year, we worked with the students who studied Didactics II as part of their Bachelor's Degree studies in Psychopedagogy at the University of Río Cuarto (Argentina). The incidental sample consisted of 41 students. The collected data was based on results from the Cognitive and Affective Empathy Test (López-Pérez et al., 2008), which considering total scores and constituent dimensions, cognitive and affective empathy. Data analysis was performed according to quantitative procedures, using the PSPP program for processing and analysis responses that were previously coded. Results highlight strengths and weaknesses of the study group regarding their empathic capacity. The group results reveal low levels of empathy –from a global perspective- and medium scores for their cognitive empathic capacity and low results for affective empathic capacity – all theoretically recommended levels-. However, a subgroup of students was perceived to have an extremely low degree of empathic capacity - both globally and within each of the aforementioned scales. Findings reflect the need to provide instructional contexts toa aid future teachers in to developing greater empathy – a skill that will benefit their professional career. Three possible actions to be carried out in the classrooms were proposed to this end: promoting opportunities for self-knowledge; promoting feedback aimed at highlighting qualities of students, providing more opportunities for social interaction.